Computer-Assisted Instruction: An Innovative Tool of Remedial Teaching for Children with Position-in-Space type of Learning Disability - Kumar, Ravindra (JOURNAL OF TEACHER EDUCATION AND RESEARCH, 2012)
Now-a-days, the computer is an innovative tool for remedial teaching of children with diverse need. In this study, the investigator investigated whether computer-assisted instruction (CAI) (games/simulations) as remedial teaching for specific position-in-space type of learning disabled children and whether CAI helps equally both boys and girls. The study adopted the pre-test– post-test-control group design. Simple random sample of 64 students were drawn from seven schools in Meerut, Uttar Pradesh, India. The researcher coordinates the CAIs (game/simulations) for position-in-space-type learning-disabled children which was used as an instrument for experimental group, whereas control group were exposed to traditional teaching method. The instrument used for data collection was diagnostic test of learning disability Diagnostic Test of Learning Disability test. The t test statistics was used to analyse the hypothesis. The findings revealed that experimental group performed better than the control group. The study found that CAI method was better than traditional method on fifth-grade position-in-space coordination learning-disabled students.